New Insights into Mesolithic Human Diet in the Mediterranean from Stable Isotope Analysis: The Sites of Campu Stefanu and Torre d'Aquila, Corsica. (16th December 2016) - Goude, G.; Willmes, M.; Wood, R.; Courtaud, P.; Leandri, F.; Cesari, J.; Grün, R.
Abstract: Mesolithic human remains are rare in the archaeological record of the French Mediterranean. Only the island of Corsica has so far produced relatively well‐preserved burials, and recent archaeological excavations have brought to light new Mesolithic human remains. The site of Campu Stefanu, located in Sollacaro in the southeast of the island, contained a collective burial of seven to eight individuals in a previously unobserved funerary context. A re‐evaluation of collections in regional museums yielded the remains from another Mesolithic individual from the site of Torre d ' Aquila, excavated at Pietracorbara, in the northern part of the island, at the beginning of the 1990s. These two discoveries presented the rare opportunity to obtain new radiocarbon dates and paleodietary insights from this crucial time period using stable isotope analysis (δ 13 C, δ 15 N) on collagen. From Campu Stefanu, one individual had sufficient collagen preserved for radiocarbon dating, revealing that it is the oldest Mesolithic human known on the island, dated to 10216–9920 cal. BP. At Torre d'Aquila, radiocarbon dates indicate that the individual belonged to a younger Mesolithic phase than Campu Stefanu, dated to 9903–9596 cal. BP. δ 13 C and δ 15 N isotope ratios are similar between the Campu Stefanu and Torre d'Aquila individuals and indicate a diet dominated by the consumption of terrestrial animal protein and a lack of marine resources. These findings are in contrast with the previous results from two other Mesolithic individuals from Corsica from the sites of Araguina Sennola and Monte Leone, for which about 25–30% of the consumed proteins came from a marine diet. The dietary variability recorded in Corsica is consistent with results obtained from Mesolithic human remains of Sicily and the Iberian Peninsula. We can hypothesise, that despite the nomadic lifestyle, the distance to the sea played a major role in Mesolithic food choices in Corsica. Copyright © 2016 John Wiley & Sons, Ltd.